Petromyzontidae‐Biomimetic Multimodal Microneedles‐Integrated Bioelectronic Catheters for Theranostic Endoscopic Surgery. (22nd January 2023) - Huang, Shuang; He, Mengyi; Yao, Chuanjie; Huang, Xinshuo; Ma, Deyuan; Huang, Qiqi; Yang, Jingbo; Liu, Fanmao; Wen, Xingqiao; Wang, Ji; Chen, Huijiuan; Xie, Xi
Abstract: Current catheter devices in minimally invasive surgery still possess limited functional options, lacking multimodal integration of both sensing and therapy. Catheter devices usually operate outside the tissue, incapable to detect intra‐tissue biochemical information for accurate localization and assessment of lesions during surgery. Inspired by the feature and functions of Petromyzontidae, here a multimodal core‐shell microneedles‐integrated bioelectronic catheter (MNIBC) for tissue‐penetrating theranostics in endoscopic surgery is developed. The microneedle (MN) device possesses individually addressable functionality at single‐MN tip resolution, enabling multiplex functions (a total of 11 functions distributed in three types of catheters) including biochemical sensing, myoelectric modulation, electroporation, and drug delivery in a submucosal environment. The MNIBC is prepared through hybrid fabrication and dimensionality reduction strategies, where the MN electrodes are functionalized with an MXene‐carbon nanotube (MXene‐CNT)‐based electron mediator, addressing the challenge of reduced electrode sensitivity on ultra‐small MN tip. The functionalities of MNIBC are demonstrated both ex vivo and in vivo on anesthetized rabbits via laparoscopy, simulated cystoscopy, and laparotomy. The MNIBC can effectively detect intra‐tissue biochemical signals in the bladder, and offers localized electroporation and intra‐tissue drug delivery for precise treatments of lesions. The versatile features of the MNIBC present a highly advanced platform for precise surgeries. Abstract : Inspired by the feature and functions of Petromyzontidae, a multimodal core‐shell microneedles‐integrated bioelectronic catheter (MNIBC) for tissue‐penetrating theranostics in endoscopic surgery is developed. The MNIBC can effectively detect intra‐tissue biochemical (both metabolites and ions) signals in minimally invasive surgery and offer localized electroporation and intra‐tissue drug delivery for precise treatments of lesions.